Health care, entitlement and citizenship - Redden, Candace Johnson (Institute of Public Administration of Canada series in public management and governance., 2002)
Redden examines the theoretical dimensions of citizenship and rights in Canada as they intersect with health care politics, and offers answers to questions concerning the right to health care and the equitable distribution of health care resources.